Breath Versus Emotions: The Impact of Different Foci of Attention During Mindfulness Meditation on the Experience of Negative and Positive Emotions. Issue 5 (September 2018) - Beblo, Thomas; Pelster, Sarah; Schilling, Christine; Kleinke, Kristian; Iffland, Benjamin; Driessen, Martin; Fernando, Silvia
Abstract: Mindfulness meditation yields beneficial effects on the processing of emotions. However, it is still unclear whether the focus of attention during meditation influences these effects. In the present study we aimed at comparing the effects of breathing meditation and emotion-focused meditation on the immediate and delayed processing of negative and positive emotions. The study included 65 adult novice meditators who were exposed to positively and negatively valenced film clips. Participants were randomly assigned to three conditions. While watching the films at t1, they were asked to mindfully focus on their breath (condition 1), on emotions (condition 2), or on nothing in particular (condition 3). Ten minutes later at t2, comparable film clips were shown but all participants watched them without taking up a mindful attitude. Dependent measures were emotional states at t1 and t2. Participants of both meditation conditions particularly showed a more preferable delayed emotional reaction to negative stimuli than participants of the control condition. Breathing meditation and emotion-focused meditation may constitute effective emotion regulation strategies to deal with negatively valenced emotional states. Highlights: Breathing meditation yields beneficial effects for negative emotions. Emotion-focused meditation tends to yield similar delayed effects. Effects primarily affected the delayed emotional response. Effects affected both, emotional valence and arousal.